Anthropometric characteristics of Roma women population in Virovitica-Podravina County, Croatia - Šegregur, Jadranko; Šegregur, Domagoj (Anthropologie, 2020)
The aim of this study was to present and compare anthropometric characteristics of Roma pregnant women in Virovitica-Podravina County to the majoritarian non-Roma group. A retrospective study on deliveries of Roma women at the Maternity Ward of the General Hospital Virovitica, Croatia, was carried out in the period from 1991 to 2010. The study included 204 Roma and 408 non-Roma pregnant women. The values analysed were prepregnancy body weight and height, body mass index (BMI), body weight before delivery, gestational weight gain (GWG) and external dimensions of the pelvis. Roma women give birth while being on average younger, 7.6 cm smaller, 4.70 kg lighter at the beginning and 5.13 kg at the end of the pregnancy, compared to the non-Roma women. The values of BMI and GWG are similar in both groups, however a higher frequency of the underweight, overweight and obese pregnant women was found in the Roma group. All three outer dimensions of the pelvis (Distancia cristarum, spinarum and trochanterica) are on average 1 cm smaller in Roma group. The differences in anthropometric characteristics between Roma and non-Roma pregnant women in Virovitica-Podravina County can be explained by ethnical origin, interaction with environmental factors and lifestyle.
Keywords: Pelvis; Roma; Body Weights and Measures; lidé; Female; Anthropometry; tělesné váhy a míry; Pregnant People; těhotné ženy; Croatia; Romové; Chorvatsko; antropometrie; ženské pohlaví; pánev; Humans